Tobacco industry sociological programs to influence public beliefs about smoking - Glantz, Stanton (2008)
The multinational tobacco companies responded to arguments about the social costs of smoking and hazards of secondhand smoke by quietly implementing the Social Costs/Social Values project (1979–1989), which relied upon the knowledge and authoritative power of social scientists to construct an alternate cultural repertoire of smoking. Social scientists created and disseminated non-health based, pro-tobacco arguments without fully acknowledging their relationship with the industry. After the U.S. Surgeon General concluded that nicotine was addictive in 1988, the industry responded by forming “Associates for Research in the Science of Enjoyment” (c.1988–1999), whose members toured the world promoting the health benefits of the use of legal substances, including tobacco, for stress relief and relaxation, without acknowledging the industry’s role. In this paper we draw on previously secret tobacco industry documents, now available on the internet to show how both of these programs utilized academic sociologists, political scientists, anthropologists, psychologists, philosophers and economists, and allowed the industry to develop and widely disseminate friendly research through credible channels. Strategies included creating favorable surveys and opinions, infusing them into the lay press and media through press releases, articles and conferences, publishing, promoting and disseminating books, commissioning and placing favorable book reviews, providing media training for book authors and organizing media tours. These programs allowed the tobacco industry to affect public and academic discourse on the social acceptability of smoking.